The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00049-011-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Chemical defense in pelagic octopus paralarvae: Tetrodotoxin alone does not protect individual paralarvae of the greater blue-ringed octopus (Hapalochlaena lunulata) from common reef predators

Abstract: Some pelagic marine larvae possess anti-predator chemical defenses. Occasionally, toxic adults imbue their young with their own defensive cocktails. We examined paralarvae of the greater blue-ringed octopus (Hapalochlaena lunulata) for the deadly neurotoxin tetrodotoxin (TTX), and if present, whether TTX conferred protection to individual paralarvae. Paralarvae of H. lunulata possessed 150 ± 17 ng TTX each. These paralarvae appeared distasteful to a variety of fish and stomatopod predators, yet food items spik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…TTX in the offspring of toxic organisms such as pufferfish, octopus, newt and flatworm, appear to be obtained by means of a vertical maternal transfer 34 39 . This maternally provided TTX provides even just-hatched larvae protection from predators 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…TTX in the offspring of toxic organisms such as pufferfish, octopus, newt and flatworm, appear to be obtained by means of a vertical maternal transfer 34 39 . This maternally provided TTX provides even just-hatched larvae protection from predators 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…467,468 The toxin involved is the potent sodium channel blocker TTX 469 that is found in the posterior salivary glands, skin, branchial hearts, gills and Needham’s sac, 470 so care should also be taken with handling these animals post mortem . Recently, TTX has been found in the eggs with the levels increasing after laying; 471 therefore, the risk with this species does not only come from adults. Other data show that the venom is produced by symbiotic bacteria ( Aeromonas , Bacillus , Pseudomonas and Vibrio ) found in the salivary glands.…”
Section: Risk Assessment For Operatorsmentioning
confidence: 99%
“…The lack of distinct puncture marks may also be an indication that the octopus may not have bitten the inner tissue of the esophagus; instead, toxins may have been leached from the dermis of H. fasciata , as proposed by Yotsu-Yamashita et al ( 2007 ). However, while TTX has been detected in high levels in multiple regions of the octopus body (Yotsu-Yamashita et al 2007 ; Williams and Caldwell 2009 ; Williams et al 2011 ), it has been shown that the consumption of tissue is fifty times less toxic relative to intraperitoneal injection (Xu et al 2003 ). The lack of detectable TTX in the seagrass bolus in which the octopus was fully encased further indicates that the TTX detected in the turtle tissues came from the octopus via active envenomation, not exudation.…”
Section: Discussionmentioning
confidence: 99%
“…This powerful technique utilizing HPLC–MS with hydrophilic interaction chromatography was chosen above single-stage mass spectrometry (SSMS). During SSMS, many other substances may elute off the column at the same retention time as TTX, making a negative control necessary (Matsumura 1995 , 2001 ; Williams et al 2004 , 2011 ). To highlight the strength of this technique, we included a negative control, although it was unnecessary as the technique provides unequivocal identification of TTX.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation